"Pedagogical and psychological preparation of preschool children for educational activities" - Ibragimova Khurshida Khusanbayevna (Genius Journals, 2023)
This article describes one of the urgent issues of the preschool education system, the issue of preparing children for educational activities from the pedagogical and psychological point of view. During the kindergarten age, age and gender characteristics have a specific character. It is shown that the age and gender characteristics have a specific character during the kindergarten age and the content of the initial educational activities of personality formation. Annotation: One of the urgent issues of the preschool education system is covered in this article: preparation of children from the pedagogical and psychological aspect of educational activities. During the kindergarten age, age and gender characteristics have their own characteristics. It is shown that the age and gender characteristics have a specific character during the kindergarten age and the content of the initial educational activities of personality formation
Keywords: education; training; educational activity